Development and Validation of the French-Canadian Chronic Pain Self-Efficacy Scale - Anaïs Lacasse; Patricia Bourgault; Yannick Tousignant-Laflamme; Roxanne Courtemanche-Harel; Manon Choinière (Pain Research and Management)
BACKGROUND: Perceived self-efficacy is a non-negligible outcome when measuring the impact of self-management interventions for chronic pain patients. However, no validated, chronic pain-specific self-efficacy scales exist for studies conducted with French-speaking populations.